Association between sources of sexuality education, sexual beliefs and behaviours in Lebanese young adults - Bouclaous, Carmel H. (2020)
This study assessed the association between sources of sexuality education, sexual beliefs and behaviour among Lebanese youth. 451 unmarried students at a private university, mean age 20.25 (±1.41) years, participated in the study. Main sources of information were teachers, mothers, internet and friends. Respondents wished for increased involvement of fathers and doctors in their sexuality education. There was a positive association between receipt of school classes on reproductive health and adoption of protective behaviour at first sexual experience (OR = 4.09, p < 0.05). A Sexual Belief Index (SBI) was calculated as a mean score on 18 items related to sexual permissiveness (Cronbach’s alpha = 0.83). Sex and classes on reproductive health predicted a rise in SBI. The timing of classes, namely earlier introduction, and communication with family and religious figures predicted a decrease in SBI. The SBI was positively associated with sexual activity (OR = 3.68, p = 4.399e-07), first sex at <17 years (OR = 5.262, p = 0.0099) and engagement in one-night stands (OR = 4.195, p = 0.0001). Students who engaged in same-sex sexual experiences had higher odds of contracting STIs (OR = 12.7, p = 0.0001). Findings reveal the need to include sexual health in school curricula; train parents, physicians and teachers as information providers and moderators of SBI; and improve access to youth-friendly services. KEYWORDS: Lebanonyouthsexual behavioursexual beliefsinformation on sexuality